Copper-doped mesoporous hydroxyapatite microspheres synthesized by a microwave-hydrothermal method using creatine phosphate as an organic phosphorus source: application in drug delivery and enhanced bone regeneration. Issue 5 (18th January 2017) - Yu, Weilin; Sun, Tuan-Wei; Ding, Zhenyu; Qi, Chao; Zhao, Huakun; Chen, Feng; Shi, Zhongmin; Zhu, Ying-Jie; Chen, Daoyun; He, Yaohua
Abstract : The Cu-MHMs show great potential in drug delivery and bone augmentation. Abstract : The development of multifunctional biomaterials with drug delivery ability, and pro-osteogenic and pro-angiogenic activities has garnered increasing interest in the field of regenerative medicine. In the present study, hypoxia-mimicking copper (Cu)-doped mesoporous hydroxyapatite (HAP) microspheres (Cu-MHMs) were successfully synthesized through a microwave-hydrothermal method by using creatine phosphate as an organic phosphorus source. The Cu-MHMs doped with 0.2, 0.5 and 1 mol% Cu were prepared. The Cu-MHMs consisting of HAP nanorods or nanosheets exhibited a hierarchically mesoporous hollow structure and a high specific surface area. Then the Cu-MHMs were investigated as a drug nanocarrier using doxorubicin hydrochloride (DOX) as a model drug. The Cu-MHMs showed a relatively high drug-loading capacity and a pH-responsive drug release behavior. Furthermore, the Cu-MHMs were incorporated into a chitosan (CS) matrix to construct a biomimetic scaffold optimized for bone regeneration. The Cu-MHM/CS composite scaffolds maintained high degrees of porosity and showed a sustained release of Cu ions. More importantly, the Cu-MHM/CS scaffolds not only enhanced the osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells (rBMSCs) but also promoted the migration and tube formation of EA.hy926 cells. When implanted in rat critical-sized calvarial defects, the Cu-MHM/CS scaffolds significantly enhanced bone regeneration accompanied by more new blood vessel formation at 8 weeks post-operation compared with the MHM/CS scaffolds. These results suggest that the hypoxia-mimicking Cu-MHM/CS scaffolds could encourage bone regeneration by enhancing osteogenesis and angiogenesis simultaneously, which bodes well for the reconstruction of vascularized tissue-engineered bone.